THE USE OF MODERN INNOVATIVE TECHNOLOGIES IN TEACHING ENGLISH (Academia Science Repository, 2023)
This article highlights the great importance given to foreign languages in the Republic of Uzbekistan and the innovative technologies necessary for learning them.